RAJA ALI HAJI'S PHILANTHROPIC THOUGHT: THE ROLE OF CULTURE AND LANGUAGE IN THE FORMATION OF URBAN MALAY IDENTITY - Rizki, Muh.; Yusdani, Yusdani; Marazi, Hamidullah; Rahmawati, Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
This article explores Raja Ali Haji's philanthropic thoughts with an emphasis on the central role of culture and language in shaping Malay identity. As a 19th century Malay intellectual, Raja Ali Haji made significant contributions to the preservation and development of Malay culture and language, as reflected in his works, such as Gurindam Dua Belas, Kitab Pengetahuan Bahasa and Bustan al-Katibbin. Through a historical and literary analysis approach, this article aims to understand the concept of Raja Ali Haji's cultural philanthropy and its impact on the formation of Malay identity. By using a historical and literary analysis approach, the aim is to understand the concept of Raja Ali Haji's cultural philanthropy and its impact on the formation of Malay identity, especially in urban communities. This research reveals that Raja Ali Haji's thoughts remain relevant in the context of preserving Malay cultural and linguistic identity in the modern era. It can be seen that the thought is implemented in Malay terms,